Indian Higher Education and Effect of COVID-19 on it - Kishor Kumar Dash (AG Volumes, 2022)
In addition, the epidemic has caused severe disruptions in the higher education sector, which is a crucial factor in determining the economic destiny of a nation. It goes without saying that the epidemic has shifted education away from the traditional chalk-and-talk paradigm and toward one that is driven by technology. Because of this upheaval in the way education is delivered, governments are being forced to find out how to stimulate participation on a massive scale while also assuring equitable e-learning solutions and addressing the digital divide. It will need a plan with several components if the crisis is to be contained and the Indian educational system is to be strengthened over the long run. Additionally, the development of young brains requires educational practises that are both comprehensive and efficient in order to be successful. It will cultivate skills that will drive their employment, productivity, health, and well-being in the decades to come, and it will also assure the general growth of India.The globe is becoming more linked, which means the threats we confront are also rising. The epidemic caused by COVID-19 has not been contained by national boundaries. It does not matter a person's country, degree of education, income, or gender; everyone has been impacted. But the same cannot be said for its effects, which have had the greatest impact on the most defenceless members of society. There is no exemption made for education. Students that come from rich families, are encouraged to study by their parents, are motivated to learn, and are capable of learning may be able to get through closed school doors and access alternative learning possibilities. People who come from impoverished circumstances are often excluded once their schools close. Because of this crisis, many flaws and inequalities in our educational systems have been brought to light. These flaws range from a lack of accessibility to the broadband and computers required for online education, to the lack of supportive environments required to concentrate on learning, all the way up to a misalignment between resources and needs.